The Tradition of Child Becungak In Cultural Values In The Kampar Community of Riau Province - Nurmalinda, Nurmalinda; Zulfa, Zulfa (Journal of Humanity Studies, 2023)
This research aims to describe in detail how the Becungak Anak tradition relates to cultural values in the Sawah Community in North Kampar District, Kampar Regency, Riau Province. The Bacungak anak tradition is a form of gratitude for the birth of a child by inviting village people and praying for the baby to always be under the protection of Allah SWT, and to develop into a child who is pious and pious and has faith and is useful for society. The research method uses descriptive qualitative methods. The data collection techniques used in this research are: observation techniques, interview techniques, and documentation study techniques. In this research, there were 6 subjects consisting of baby midwives, baby parents, babies, the general public and local traditional leaders. The main resource person in this research is Mak Oncu Asmarni as a baby midwife or leader of the Becungak Anak tradition. The implementation of the becungak anak tradition is as follows: becungak anak is seen in terms of i) time, ii) place, iii) objects/tools, iv) people involved in it. From the results of this research, it was found that the values contained in children's Becungak are: religious values, social values, and also traditional values. Apart from that, the Becungak Anak Procession is still preserved among the people of Sawah Village, North Kampar District, Kampar Regency, Riau Province. The becungak anak tradition is a tradition that has cultural values that must be preserved in Kampar society, so that these cultural values remain alive in Kampar society in particular and Riau society in general.